Relação da comunidade de formigas (hymenoptera: formicidae) a fatores microclimáticos e de paisagem no leste maranhense - CONCEIÇÃO, Camila Braga da (2022)
Landscape modifications are linked to anthropogenic effects that lead to changes in ecosystem dynamics and habitat loss. Fire is one of the elements that shape the formation of the landscape, the indiscriminate practice of burning provides the homogenization of the environment. These changes, consequently, affect the species composition that perform important services in the ecosystems maintenance, and can be diagnosed through the use of bioindicator insects, such as ants. This study aimed to evaluate the association of ants with microclimatic and landscape variables in a cerrado area in eastern Maranhão. We delimited 20 sampling points in burned areas, little burned and unburned, distant approximately 450m. To collect the ants we distributed five soil traps (pitfall) per point, distant 20m from each other. We collected local environmental data from the heights of grasses, shrubs and litter, and tree density. We used landscape variables of vegetation cover and number fire foci. We inventoried 97 species/morphospecies of ants, with seven new records for the first time in Maranhão. In the vegetation analyses, the ants composition was associated with grass heights and tree density, and in landscape analysis the composition of ants was associated with the fire foci. We conclude that grasses, tree density and fire foci are important factors in the structuring of the ant community. Grasses and trees can offer niches with a greater variety of food resources and nesting sites that contribute to species composition and diversity. Our study provides grounds for the use of genera in environmental studies. We also emphasize the importance of habitat conservation in order to ensure the richness and diversity of species in Cerrado areas.